Effects of Yu-Ping-Feng polysaccharides on animal growth performance and immune function: a review - Chu, Huangbin; Zong, Yi; Yang, Hong; Chen, Siyu; Ma, Zheng; Li, Hua (Frontiers in Veterinary Science, 2023)
Yu-Ping-Feng polysaccharides (YPF-P) is the primary component of Yu-Ping-Feng San (YPF-S) remedy, renowned for its efficacy in enhancing the body's immune system and defending against foreign pathogens. This review mainly introduces the main components and characteristics of Yu-Ping-Feng polysaccharides, its effects on animal production, and its impact on animal immune function. It aims to provide breeding enterprises with valuable references and insights to reduce production costs and enhance production efficiency.